Spray-type packed bed concept for thermal energy storage: Liquid holdup and energy storage characteristics. (September 2019) - Xie, Ningning; Wang, Liang; Wang, Yifei; Lin, Xipeng; Lin, Lin; Ji, Lyu; Sheng, Yong; Chen, Haisheng
Highlights: A new spray-type packed bed thermal energy storage technology is proposed. Liquid holdup inside spray-type packed bed can be minimized to 0.1. The practicability of spray-type packed bed thermal storage technology is verified. The cost of spray-type packed bed can be below 13.0 $/kWh. Abstract: The performance of a thermal energy storage system strongly influences the overall efficiency of a central solar power plant. Therefore, low-cost and high-efficiency thermal energy storage technologies have attracted considerable attention in recent years. A thermal energy storage concept using a spray-type packed bed is proposed in the present study. In addition, a small-scale semi-transparent spray-type packed bed thermal storage system was set up, using thermal oil as a transfer fluid and spherical particles as the storage media inside the packed bed. An experimental study on the liquid holdup and heat storage characteristics of the proposed spray-type packed bed system was conducted. The results indicate that the total liquid holdup increases as the volume flow rate increases, and the static liquid holdup inside the packed bed shows no relationship with the flow rate or height of the packed bed. Herein, a comparison of the unit cost for different thermal energy storage technologies is presented.